Reconhecimento e alteridade: haitianos em Lajeado - Ortiz, Letícia Rossi (2018)
Haitian migration to Brazil is a new contemporary migratory flows, which includes, in addition to the intensification of the phenomenon, a diversification of origins and destinations. At the end of the year 2012, a route between Haiti and Lajeado was inaugurates. Lajeado is a city of approximately 80 thousand inhabitants localized in the region of Vale do Taquari, in Rio Grande do Sul, Brazil. It is a city formed from historical migrations, mainly German and Italian, but also Portuguese and African to a lesser extent. The beginning of the Haitian flow is attributes to the interest of companies in the region in the workforce of this population that was been entering Brazil since the north of the country since 2010. Since then, this flow has become dynamic and independent of local economic interests. This dissertation addresses aspects of the encountering between this migrant population and the established population focusing on the relations of alterity and the subjective demands for recognition generated from the immigrant condition experienced by the population in mobility when confronting the stereotypes and the stigmas elaborate on then. We identified three key values of these subjective demands for recognition: the search for trust, the fight against a mistaken view of illegality and the valorization of intellectual competencies and labor competencies beyond manual labor.